Interpreting Fiscal Risk for Lack of Bank Indonesia’s Capital - Yuli Indrawati (Jurnal Media Hukum, 2021)
The research is focused on determining the government's obligation to meet the shortage of capital of Bank Indonesia (BI), as the central bank, in the National State Budget (APBN). The research analyzes the basis of the government's obligation to meet BI's lack of capital and a mechanism for fulfilling the government's obligations to cover BI deficiencies in line with the objectives of the APBN. This study uses a normative legal research method with a statute, interdisciplinary, and analytical approach. The result shows that the government's obligation to suffice BI's capital is intended to maintain BI's sustainability so that BI can continue to carry out its responsibilities and obligations to maintain monetary stability. Monetary stability has implications for economic stability and increases in people's welfare. In addition, the fulfilment of government obligations is contingent, limited and final. This obligation will only be born if BI is no longer able to overcome the lack of capital. The cause of the lack of capital is beyond BI's control, as evidenced by the results of an examination by the Supreme Audit Agency and requires the approval of the House of Representatives.